Cardiosphere-Derived Cells Attenuate Inflammation, Preserve Systolic Function, and Prevent Adverse Remodeling in Rat Hearts With Experimental Autoimmune Myocarditis. (January 2019) - Nana-Leventaki, E.; Nana, M.; Poulianitis, N.; Sampaziotis, D.; Perrea, D.; Sanoudou, D.; Rontogianni, D.; Malliaras, K.
Background: Cardiosphere-derived cells (CDCs) have yielded promising efficacy signals in early-phase clinical trials of ischemic and nonischemic cardiomyopathy. The potential efficacy of CDCs in acute myocarditis, an inflammatory cardiomyopathy without effective therapy, remains unexplored. Given that CDCs produce regenerative, cardioprotective, anti-inflammatory, and anti-fibrotic effects (all of which could be beneficial in acute myocarditis), we investigated the efficacy of intracoronary delivery of CDCs in a rat model of experimental autoimmune myocarditis. Methods: Lewis rats underwent induction of experimental autoimmune myocarditis by subcutaneous footpad injection of purified porcine cardiac myosin supplemented with Mycobacterium tuberculosis on days 1 and 7. On day 10, rats were randomly assigned to receive global intracoronary delivery of 500 000 CDCs or vehicle. Global intracoronary delivery was performed by injection of cells or vehicle into the left ventricular (LV) cavity during transient occlusion of the aortic root. Rats were euthanized 18 days after infusion. Cardiac volumes and systolic function were assessed by serial echocardiography, performed on days 1, 10, and 28. Myocardial inflammation, T-cell infiltration, and cardiac fibrosis were evaluated by histology. Results: Experimental autoimmune myocarditis was successfully induced in 14/14 rats that completed follow-up. Left ventricular ejection fraction (LVEF) and volumes were comparable on days 1 and 10 between groups. CDC infusion resulted in increased LVEF (81.5% ± 3% vs 65.4% ± 8%, P < .001) and decreased LV end-systolic volume (43 ± 15 vs 100 ± 24 μL, P < .001) compared to placebo administration at 18 days post-infusion. Cardiosphere-derived cell infusion decreased myocardial inflammation (7.4% ± 7% vs 20.7% ± 4% of myocardium, P = .007), cardiac fibrosis (16.6% ± 13% vs 38.1% ± 3% of myocardium, P = .008), and myocardial T-cell infiltration (30.4 ± 29 vs 125.8 ± 49 cells per field, P = .005) at 18 days post-infusion compared to placebo administration. Conclusion: Intracoronary delivery of CDCs attenuates myocardial inflammation, T-cell infiltration, and fibrosis while preventing myocarditis-induced systolic dysfunction and adverse remodeling in rats with experimental autoimmune myocarditis.